Canva easy to use!! / Azlina Mohd Mydin... [et al.] - Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Johan, Elly Johana; Kechil, Rafizah (Unit Penerbitan Dan Publisiti JSKM, 2022)
Canva are a design platform, used to create social media graphics,presentations, posters, documents and other visual content. They are variety of template provided. Below the different form of design provided in Canva.